AB0138 Mice lacking the alpha 7 nicotinic acetylcholine receptor have increased bone mass. (23rd January 2014) - Mandl, P.; Hayer, S.; Huck, S.; Niederreiter, B.; Scholze, P.; Sykoutri, D.; Smolen, J.S.; Redlich, K.
Abstract : Background: Cholinergic receptors, discovered on bone cells suggest that the cholinergic nervous system may play a regulatory role also in bone metabolism. Our previous experiments have confirmed the presence of nicotinic acetylcholine receptor subunits on osteoclasts, and have revealed that the α7 nicotinic acetylcholine receptor plays a key role in the regulation of osteoclastogenesis in vitro . Objectives: To evaluate the role of the α7 nicotinic acetylcholine receptor in bone homeostasis in vivo . Methods: We analyzed the bone phenotype of α7 nicotinic acetylcholine receptor knockout mice (α7 nAChR -/- mice). We investigated the bone phenotype of C57/BL6 α7 nAChR -/- mice as well as sex- and age-matched littermates. For bone mineral density (BMD) measurements we evaluated the proximal tibia and BMD values were calculated by using dual energy X-ray absorptiometry (DEXA). Bone phenotype was further evaluated by histomorphometrical analysis using 2-μm decalcified paraffin-embedded sections stained with hematoxylin and eosin, toluidine blue, and TRAP. Histomorphometry of metaphyses was performed using an Axioskop 2 microscope and OsteoMeasure Analysis System (OsteoMetrics) according to international standards. Results: We observed no marked macroscopic alterations suggestive of a severe osteopetrotic phenotype (disturbed teeth eruption, shortened limbs) in α7 nAChR -/- mice. However, DEXA revealed a significantly increased trabecular density (+26%) in 16 week old male α7 nAChR -/- mice compared to wild-type littermates. In line with this finding, histomorphometry of α7 nAChR -/- mice also showed increased bone volume/tissuevolume (p≤0.001) as well as increased trabecular thickness (p≤0.001), coupled with reduced trabecular separation (p≤0.001). To further evaluate the pathomechanisms involved, we elaborated the effects of α7 nAChR on both osteoclasts and osteoblasts. In α7 nAChR -/- mice we found a reduced number of osteoclasts/bone perimeter (p≤0.001) and reduced osteoclast surface/bone surface (p≤0.05), whereas osteoblasts were not affected. Conclusions: Our investigations have revealed increased bone mass coupled with reduced osteoclastogenesis in mice lacking the α7 nicotinic acetylcholine receptor subunit. These findings confirm the significance of these receptors in osteoclastogenesis and highlight the important regulatory role of the cholinergic nervous system in bone turnover. Disclosure of Interest: None Declared